The Development of Posters as PAI Learning Media for Students with Intellectual Disabilities at SLB Negeri Sabang - Nasrizal, Nasrizal; Saiful, Saiful; Masya, Saifullah (Jurnal Ilmiah Teunuleh, 2026)
Students with disabilities often have difficulty understanding Islamic Religious Education (PAI) material which tends to be abstract, such as the concept of monotheism, morals, and worship procedures. Limited memory, language skills, and low focus on learning result in less optimal learning and decreased learning motivation. Learning media that is not in accordance with the characteristics of students further exacerbates the gap in understanding. This research aims to develop posters as PAI learning media for students with disabilities in SLB Negeri 1 and 2 Sabang. The method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. Data analysis was carried out using the Miles and Huberman interactive model, while the validity of the data was ensured through diligence of observation and triangulation of sources. The results showed that posters designed with simple visuals, short text, and contrasting colors effectively simplified abstract concepts into concrete forms, improved memory, motivated students, and facilitated alternative communication. Participatory evaluation involves teachers, students, and parents, with success indicators including increased understanding, engagement, and positive behavior change. This study recommends the sustainable use of posters with design and content improvements based on regular evaluations, to support inclusive and meaningful PAI learning for students with disabilities.